Multiple-Antibiotic Resistance Mediated by Plasmids and Integrons in Uropathogenic Escherichia coli and Klebsiella pneumoniae - Lina, Taslima Taher; Rahman, Sabita Rezwana; Gomes, Donald James (Bangladesh Journal of Microbiology, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <mce:style><! st1\:*behavior:url(#ieooui) –> <!–[endif] –> <!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400; –> <!–[endif] –> Antibiotic resistance in urinary tract infection (UTI) is a growing public health problem in the world. In this study, a total of 182 uropathogens were isolated from patients with symptoms of urinary tract infection (UTI). Escherichia coli (88%) was the most prevalent isolate, while Klebsiella pneumoniae was recovered from 12% cases. The male/female ratio was 1:3. About 56% female and 51% male patients belonged to the age group >40 years. The antibiotic resistance rates of the isolates to fifteen different drugs were investigated. E. coli and K. pneumoniae showed variable pattern of susceptibility. The percentage of resistance to different drugs was higher in E. coli isolates compared to that of K. pneumoniae. Among the total number of isolates about 87% were resistant to at least three commonly used antibiotics. All the isolates were sensitive to imipenem. Analysis of the plasmid DNA had shown that the plasmid pattern was very diverse in both E. coli and K. pneumoniae. All the isolates contained multiple numbers of plasmid ranging from 1.0 to >140 MDa. Middleranged plasmids (30 to 80 MDa), the transferable resistance plasmids, were found to be present in 86% E. coli and 85% K. pneumoniae isolates. The strong association observed between plasmid profiles and drug resistance patterns suggest that plasmids other than the common plasmids may have epidemiological significance. The presence of class 1 and class 2 integrons were also investigated. A relatively high occurrence of class 1 integrons, that are associated with lateral transfer of antibacterial resistance genes, was observed in K. pneumoniae (88%) than in E. coli isolates (54%). Class 2 integrons were not found in any of the E. coli and K. pneumoniae isolates. These results show the high rate of drug resistance and the presence of high rate of transferable elements in these MDR isolates. Keywords: Uropathogens, Escherichia coli, Klebsiella pneumoniae, Multidrug-resistant (MDR) bacteria, Plasmid profiles, Integrons DOI: http://dx.doi.org/10.3329/bjm.v24i1.1231 Bangladesh J Microbiol, Volume 24, Number 1, June 2007, pp 19-23